Supply and demand for cereals in Nepal, 2010-2030 - Prasad, Sanjay K.; Pullabhotla, Hemant; Ganesh-Kumar, Anand (International Food Policy Research Institute, 2011)
This paper attempts to estimate the future supply and demand for cereals in Nepal. While there has been considerable research in the past examining the agricultural sector in Nepal, to the best of our knowledge there has been no analysis of the supply-demand scenario for food grains in the country. The analysis undertaken in this paper attempts to bridge this gap in the literature by estimating supply and demand models for the three most important cereals in Nepal's food basket: rice, wheat, and maize. The supply projections have been carried out on the basis of a single-crop production function model using data for the period 1995-2008. For estimating the demand function and projecting future demand, data from the Nepal Living Standards Survey II (NLSS II), undertaken in the year 2003/04, are used.